The Effect of Product Diversification on Consumer Satisfaction of Bapak N'dut Pandeglang Roasted Coffee - Heru Wicaksono; Marsalino Marsalino; Indah Nurul Hudaini (Jurnal Multidisiplin Sahombu, 2026)
The habit of Indonesians who love to engage in conversations about various topics from work, daily life, to personal updates has made coffee shops a favorite gathering place. This phenomenon is further supported by the comfortable atmosphere created by soothing background music, along with the implementation of work from anywhere policies by several companies. As a result, drinking coffee has now become part of a modern lifestyle. One place that has successfully embraced this trend is Kopi Bakar Bapak N’dut in Pandeglang. This coffee shop is quite popular among tourists for its distinctive, strong, and flavorful coffee that helps relieve fatigue after a long day. Unlike modern coffee shops that serve espresso, mocaccino, or Americano. The identified problems include the limited variety of food and beverage products offered by Kopi Bakar Bapak N’dut Pandeglang, as well as the slow service perceived by customers. The research method used in this study is a quantitative approach. This study aims to verify the issues stated in the problem formulation, namely to describe and analyze the influence of product diversification on customer satisfaction at Kopi Bakar Bapak N’dut Pandeglang. Kopi Bakar Bapak N’dut maintains its traditional authenticity by offering local coffee variants such as Cofielamure, Nampuyak Kopi, and Baliung Kopi. All of these beverages are prepared manually using traditional brewing techniques passed down through generations, giving customers an authentic and nostalgic coffee experience. This study focuses on three main research questions: (1) How is product diversification implemented at Kopi Bakar Bapak N’dut Pandeglang? (2) How satisfied are customers with the products offered? and (3) To what extent does product diversification influence customer satisfaction?. The results show that the average score for respondents’ responses regarding Product Diversification is 2.85, which falls under the good category. Meanwhile, the average score for Customer Satisfaction is 2.81, also classified as good. Based on statistical analysis, the correlation between the two variables reached 86.4%, indicating that product diversification significantly influences customer satisfaction at Kopi Bakar Bapak N’dut Pandeglang. Thus, it can be concluded that the more diverse and creative the products offered, the higher the level of customer satisfaction. The remaining 13.6% is influenced by other factors not examined in this study, such as price, service quality, location, or atmosphere. These findings suggest that Kopi Bakar Bapak N’dut’s strategy of preserving traditional flavors while diversifying its product offerings has proven effective in attracting and retaining customers amid the increasingly competitive coffee industry.